Cross-cultural differences in resolving sacrificial dilemmas: choices made and how they relate to judgments of their social acceptability - Jiang, Xinyu; Harvey, Nigel (Frontiers in Psychology, 2025)
Samples of English and Chinese people judged the likelihood that they would sacrifice the life (or health) of one person to save the life (or health) of five people by performing an impersonal action (flipping a switch) or a personal one (pushing someone over a bridge). They also judged how many people out of 100 would consider their choice to be morally acceptable. Judgments by people in the two cultures were similar in two ways. First and consistently with previous work, people in both groups were more likely to sacrifice one life to save five when the action was impersonal; however, they were no more likely to make that sacrifice to save the health of five people than to save the lives of those people. Second, the likelihood of people in both cultures deciding on a sacrificial action was less than their assessments of the likelihood that such an action was morally acceptable, a result that is the opposite of what has been previously found. This contrast can be explained by recognizing the difference between asking people to assess how acceptable moral choices are to participants themselves (previous reports) and asking them to judge how acceptable those choices are to other people (this report). The two cultures also differed in two ways. Chinese participants (a) showed a larger difference between the likelihood of people acting and their assessments of the likelihood that acting would be acceptable to others, and (b) were less likely to act in impersonal dilemmas. These cross-cultural differences imply that Chinese participants were more influenced by their judgments of what other people would think about sacrificial action.